Video analysis of anterior cruciate ligament injury situations in the women`s Australian football league - Rolley, T. L.; Saunders, N.; Bonacci, J.; Keast, M.; Fox, A. S. (Science and Medicine in Football, 2023)
Background: Anterior cruciate ligament (ACL) injury rates in the Women`s Australian Football League (AFLW) are alarmingly high. Understanding injuries within their sporting context is important to develop effective injury prevention strategies, yet there is currently little knowledge of how ACL injuries occur to AFLW players. This study addressed the common scenarios and characteristics of AFLW ACL injuries. Methods: Online match and AFLW club injury reports identified 38 ACL injury cases. After excluding injuries where footage was unavailable (i.e. training, pre-season games), a video analysis of 21 match ACL injuries from the 2017-2020 AFLW seasons was performed. We examined match characteristics, and the player`s movements and body postures preceding and at the estimated time of injury. Descriptive frequencies and relative proportions were determined across the assessed categories. Results: Non-contact ACL injuries were frequently observed (n = 13, 61.9%), while contact preceding the injury event (i.e. indirect contact) was also common (n = 10, 47.6%). The most common game situation was direct defence (i.e. defending an opponent in possession) (n = 14, 66.7%). Sidestep cutting was the most prevalent movement (n = 11, 52.4%), with this commonly performed while applying defensive pressure (n = 6 of 11, 54.6%). Conclusion: Sidestep cutting when applying defensive pressure is the most common non-contact ACL injury scenario in the AFLW. Preceding contact potentially contributing to a player`s loss of balance was another prominent AFLW scenario. AFLW players may benefit from injury prevention programs emphasising appropriate sidestep cutting technique during reactive defensive scenarios, and maintenance of lower limb postures known to withstand knee loading relative to the sporting task.